2019
DOI: 10.1016/j.hrtlng.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and clinical outcomes associated with use of one-way speaking valves on tracheostomised patients: A systematic review

Abstract: Background: The one-way speaking valve was first engineered in 1985 to allow patients with tracheostomy tubes to communicate. The research has indicated alternative physiological benefits of using a speaking valve, however this literature has not yet been evaluated. The purpose of this systematic review is to evaluate the evidence for the one-way speaking valve in relation to a range of physiological and clinical domains including vital signs, aspiration, olfaction, ventilation and tracheostomy weaning, hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 21 publications
1
14
0
2
Order By: Relevance
“…On the one hand, this procedure helps patients to practice breathing through the upper airway. On the other hand, the restoration of the physiological air flow is likely to result in a restitution of the pharyngeal and laryngeal sensitivity with consecutively improved secretion management [ 135 ]. In a proof-of-principle study recruiting 20 tracheotomized stroke patients, Ledl and Ullrich showed that while capping of the tracheal cannula did not induce any changes in swallowing mechanics, swallowing safety improved resulting in lower Penetration-Aspiration-Scale scores [ 136 ].…”
Section: Diagnosticsmentioning
confidence: 99%
“…On the one hand, this procedure helps patients to practice breathing through the upper airway. On the other hand, the restoration of the physiological air flow is likely to result in a restitution of the pharyngeal and laryngeal sensitivity with consecutively improved secretion management [ 135 ]. In a proof-of-principle study recruiting 20 tracheotomized stroke patients, Ledl and Ullrich showed that while capping of the tracheal cannula did not induce any changes in swallowing mechanics, swallowing safety improved resulting in lower Penetration-Aspiration-Scale scores [ 136 ].…”
Section: Diagnosticsmentioning
confidence: 99%
“…In previous studies, the use of oneway speaking valves showed improvements in ventilation (through changes in end-expiratory lung volumes) and a reduction in RR as a secondary result of improved ventilation. 15 Previous studies 8,13,32 have also demonstrated that the use of a one-way speaking valve provides additional PEEP, which correlates with improvements in ventilation. The recruitment of additional alveoli (that occurs with increased PEEP) provides an increased surface area for oxygen diffusion to occur, thereby improving oxygenation.…”
Section: Discussionmentioning
confidence: 98%
“…7,8 Others have reported that one-way speaking valves also improve olfaction, 9e11 secretion management, 9,12 ventilation, 8,13 and quality of life. 14 In a recent systematic review 15 the evidence for using one-way speaking valves, across a number of physiological domains including vital signs, aspiration, olfaction, ventilation and tracheostomy weaning, length of stay, and quality of life was evaluated. Whilst the evidence was not strong to support the additional physiological benefits, all studies favoured the use of a one-way speaking valve (compared with no speaking valve) or reported improvements that were not statistically significant.…”
Section: Introductionmentioning
confidence: 99%
“…A comunicação no paciente traqueostomizado foi citada em três estudos 2,4,7 . Uma recente revisão sistemática com meta-análise reforça os benefícios no uso da válvula de fala, incluindo melhora no olfato, gerenciamento de secreção, ventilação e qualidade de vida, além de redução de aspiração 15 . Por outro lado, ainda há controvérsias sobre o momento adequado para o uso da válvula de fala em pacientes com COVID-19.…”
Section: Conclusãounclassified